High-strength chlorinated polyvinyl chloride material and preparation method thereof
By combining inorganic particles and organic silicon oxygen crosslinkers in chlorinated polyvinyl chloride material, chemical modification and physical blending are solved, and the problems of insufficient impact resistance and brittleness of low temperature are significantly improved, achieving significant improvements in strength, toughness and thermal stability.
Patent Information
- Application Number
- CN202411899818.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
While improving strength, plasticity and toughness, existing chlorinated polyvinyl chloride materials have insufficient impact resistance and become brittle at low temperatures, which limits their application prospects.
By combining inorganic particles with chlorinated polyvinyl chloride crosslinked by silicone oxygen, chemical modification and physical blending method, grafting hydroxypropyl methylcellulose ether and blocking acrylate, the organosiloxane-inorganic nanoparticles are further crosslinked to improve the strength and impact resistance of the material.
It significantly improves the strength, impact resistance and thermal stability of chlorinated polyvinyl chloride materials, improves low-temperature performance, and extends its application range.
Smart Images

Figure BDA0005202850830000171 
Figure BDA0005202850830000182 
Figure BDA0005202850830000191
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, in particular to a method for preparing a high-strength chlorinated polyvinyl chloride material. Background Art
[0002] Chlorinated polyvinyl chloride (CPPVC) is produced by chlorinating polyvinyl chloride (PVC). This chlorination increases the chlorine content of the material from 56.7% to 63%-68%, thereby increasing the polarity of the molecular bonds, strengthening intermolecular forces, and enhancing chemical stability. This significantly improves the material's mechanical properties, chemical corrosion resistance, and flame retardancy. However, while the increased chlorine content improves some properties, it also exhibits deficiencies in others. Due to the high melt viscosity and difficulty in molding, CPPVC products exhibit poor surface finish and impact resistance. While the material's heat resistance is improved, its thermal stability is low, and its processing properties are poor. These deficiencies significantly limit the application prospects of CPPVC resins.
[0003] At present, domestic and foreign researchers are focusing on large-scale modification research of chlorinated polyvinyl chloride in order to improve the defects of its products such as poor surface finish and poor impact resistance.
[0004] Chinese patent publication number CN113683851B discloses a method for improving the processing properties of chlorinated polyvinyl chloride (CPCV) resins. This invention uses ultra-high molecular weight chlorinated polyethylene (UHMWPE) as a processing modifier for the CPCV resin, resulting in a mixture with excellent demolding properties and enhanced toughness without affecting the Vicat softening point. While this method improves the processing properties and toughness of the CPCV resin, it also increases its brittleness as the chlorine content of the CPCV increases, leading to lower impact strength of the resulting product and increased tendency to form microcracks during deformation.
[0005] The Chinese patent with publication number CN114149649B discloses a high-strength insulating CPV material and its preparation method. The raw materials include chlorinated polyvinyl chloride, coated modified carbon black, thermally conductive filler, impact modifier, thermal stabilizer, flame retardant, internal lubricant and external lubricant. The present invention not only achieves the synergistic toughening of CPV by inorganic rigid bodies and organic elastomers through the innovative combination of filler selection and modification method, but also optimizes the structural adjustment of the filler dispersion. The invention uses the elastomeric properties of polyacrylate to further toughen the CPV material. However, although polyacrylate can improve the toughness of CPV material, it will affect the tensile strength of CPV material, especially when the ambient temperature changes greatly, it will become brittle at low temperatures.
[0006] Therefore, how to improve the strength, plasticity and toughness of CPVC while also enhancing its impact resistance and improving its low-temperature brittleness is a hot topic and difficulty in current research. Summary of the Invention
[0007] In order to solve the above problems, the purpose of the present invention is to provide a high-strength chlorinated polyvinyl chloride material to solve one or more technical problems existing in the prior art and at least provide a beneficial choice or create conditions.
[0008] The object of the present invention is achieved by the following technical solution: a high-strength chlorinated polyvinyl chloride material is prepared from the following raw materials in parts by mass: 100-120 parts of inorganic particles-organic silicon-oxygen cross-linked chlorinated polyvinyl chloride; 8-10 parts of stabilizer; 4.0-6.0 parts of composite lubricant; 0.3-0.5 parts of antioxidant; 1.5-2.5 parts of pigment;
[0009] The stabilizer is at least one of an organic tin stabilizer and a calcium zinc stabilizer;
[0010] The composite lubricant is prepared by mixing oxidized polyethylene wax and ethylene bisstearamide in a mass ratio of 1:1-2.
[0011] The antioxidant includes at least one of p-diisooctyldiphenylamine and 2,6-tert-butyl-4-methylphenol; and the pigment is titanium dioxide.
[0012] The inorganic particle-organic silicon-oxygen cross-linked chlorinated polyvinyl chloride is prepared from a chlorinated polyvinyl chloride matrix, organosiloxane, and inorganic nanoparticles. The chlorinated polyvinyl chloride matrix is prepared by chlorinating polyvinyl chloride, blocking acrylate, and grafting hydroxypropyl methylcellulose ether.
[0013] First, prepare the chlorinated polyvinyl chloride matrix, specifically:
[0014] S001: Add polyvinyl chloride powder and deionized water to a reactor, stir and mix to obtain a uniform suspension, introduce nitrogen to remove air from the reactor, use a vacuum pump to evacuate the gas in the reactor to negative pressure, slowly raise the temperature to 85-90°C, then dropwise add tert-butyl peroxybenzoate as an initiator, introduce chlorine, and allow the polyvinyl chloride and chlorine to react under a certain pressure. After reacting for 150-200 minutes, add cyclohexyl methacrylate and octadecyl (meth)acrylate, stir evenly, slowly raise the temperature to 95-100°C, introduce chlorine for a second time, add hydroxypropyl methylcellulose ether, and continue the reaction for 5-7 hours to obtain a crude product.
[0015] Among them, chlorine is initially passed through at a rate of 1.8 to 2.1 kg / min, and the pressure in the kettle is controlled at 0.5 to 0.6 MPa; the second chlorination is carried out at a rate of 3.8 to 4.2 kg / min, the heating rate is controlled at 0.07 to 0.12°C / min, the temperature is raised to 95 to 100°C, and the pressure in the kettle is controlled at 0.6 to 1.0 MPa.
[0016] S002. After the reaction is complete, stop heating. When the reaction temperature drops to room temperature, blow out the remaining chlorine with nitrogen and allow it to be absorbed in an alkali solution tank. Remove the crude product, add a certain amount of dilute alkali solution, stir for 5 minutes, then rinse with distilled water. Measure the pH value of the washing solution with pH test paper. When the washing solution is neutral, filter it, pour tetrahydrofuran into it to completely dissolve it, then add methanol to thoroughly precipitate it, and filter it again. This yields chlorinated polyvinyl chloride (CPCV) with hydroxypropyl methylcellulose ether grafted onto the blocked acrylate side chains, which is designated as CPCV. Finally, place it in a vacuum drying oven and dry it at 60±2°C to constant weight.
[0017] The invention comprises 100 to 120 parts of polyvinyl chloride powder, 1 to 2 parts of tert-butyl perbenzoate, and 150 to 250 parts of deionized water; the mass ratio of hydroxypropyl methylcellulose ether, cyclohexyl methacrylate, octadecyl (meth)acrylate, and polyvinyl chloride powder is 5 to 8:8 to 15:10 to 20:100 to 120;
[0018] During the chlorination process, in addition to substitution reactions, several side reactions also occur, resulting in abnormal structures in the CPVC molecular chain, such as head-to-head structures, unsaturated double bonds, unstable chlorine structures, and branched chains. Excessive chlorine content leads to the release of hydrogen chloride gas during processing, significantly reducing thermal stability. It also significantly strengthens the forces between the CPVC resin molecular chains, making the material less likely to denature and absorb energy when subjected to external impact, resulting in greater brittleness and poor impact resistance. However, adding an appropriate amount of acrylate monomer copolymer blocks can simultaneously improve the flexural strength of the modified CPVC, reduce melt viscosity, broaden the processing temperature range, and enhance processing performance. However, due to compatibility issues between acrylate monomers and chlorinated polyvinyl chloride, the distribution of chlorine within the matrix is uneven. We discovered that after cross-linking acrylate monomers and chlorinated polyvinyl chloride, there are large voids within the microstructure, allowing for large amounts of filling with other additives. To address the problem of uniform distribution of chlorine on the resin surface and within, we grafted hydroxypropyl methylcellulose ether, allowing hydroxypropyl methylcellulose ether to serve as cross-linking points, filling the internal pores and further cross-linking the chlorine, making the distribution of chlorine within the matrix more uniform. Furthermore, the addition of hydroxypropyl methylcellulose ether can effectively increase its elongation at break, causing the system's fracture mechanism to undergo a brittle-to-ductile transition, improving stretchability and resulting in a good surface finish for the finished product.
[0019] When the copolymer matrix obtained by block-polymerizing chlorinated polyvinyl chloride with cyclohexyl methacrylate and octadecyl (meth)acrylate is grafted with hydroxypropyl methylcellulose ether, the plasticizing time can be significantly shortened, the melting speed can be accelerated, the plasticizing can be promoted, the plasticizing of the product can be made uniform, and the surface gloss of the product can be improved.
[0020] However, because acrylate monomers are flexible particles with low inherent strength, adding them to chlorinated polyvinyl chloride (CPVC) reduces the strength of the mixture. Furthermore, due to compatibility issues, even if hydroxypropyl methylcellulose ether is grafted to solve the chlorine distribution problem, the addition of acrylate monomers disrupts the continuity of the matrix, resulting in a reduction in strength, which is particularly noticeable when the acrylate monomer content is high.
[0021] In order to solve the problem of reduced strength after block acrylate monomer, we further used organosiloxane-inorganic nanoparticles as a strength enhancer. The preparation method is as follows:
[0022] S101, in a reaction kettle equipped with a stirring paddle, a thermometer, and a condenser, vinyl trimethoxysiloxane, mono (meth)acrylate-terminated polysiloxane, and aniline methyl triethoxysiloxane are mixed with an appropriate amount of ethyl acetate and stirred evenly. Then, an initiator, azobisisobutyronitrile, is added dropwise, and the temperature is raised to 80-90° C. to react for 18-20 hours. The reaction is stopped, cooled to room temperature, and low-temperature drying is performed to remove residual small molecules in the reaction system, thereby obtaining an organosilicon polycondensate with a molecular weight of 30,000-40,000.
[0023] S102, mixing the inorganic nanoparticles and the organosilicon polycondensate in an alcohol ether solution by a solution blending method, stirring at high speed for 60 minutes, so that the inorganic nanoparticles are fully cross-linked in the organosilicon polycondensate, to obtain organosiloxane-inorganic nanoparticles;
[0024] The inorganic nanoparticles are a mixture of nano-SiO2 and graphene oxide, and the particle size is 20 to 30 nm. The preparation method is as follows:
[0025] S201, dispersing graphene oxide in water, adjusting the pH to alkaline with a NaOH solution to obtain a mixed solution; then transferring the mixed solution into a polytetrafluoroethylene hydrothermal reactor for a hydrothermal reaction to obtain two-dimensional reduced graphene oxide;
[0026] S202, converting the two-dimensional reduced graphene oxide into three-dimensional reduced graphene oxide by freeze drying, specifically as follows: freeze drying the two-dimensional reduced graphene oxide in a freeze dryer at a temperature of -30°C to -40°C for 48 hours, and grinding to obtain three-dimensional reduced graphene oxide;
[0027] S203, mixing nano-SiO2 and three-dimensional reduced graphene oxide in a mass ratio of 3:1 to obtain inorganic nanoparticles;
[0028] The mass ratio of the mono(meth)acrylate-terminated polysiloxane, anilinemethyl triethoxysiloxane and vinyl trimethoxysiloxane is 1:2:2; the mass content of the nano-silicon dioxide is 10-20% of the organosilicon polycondensate; the amount of the initiator azobisisobutyronitrile is 1-2% of the total amount of the siloxane;
[0029] Furthermore, organosiloxane-inorganic nanoparticles are added to the chlorinated polyvinyl chloride matrix to obtain inorganic particle-organosiloxane oxygen cross-linked chlorinated polyvinyl chloride, specifically:
[0030] Adding a chlorinated polyvinyl chloride matrix and organosiloxane-inorganic nanoparticles to a reaction kettle, heating the reaction kettle to 130-180° C. under nitrogen protection and stirring at 500 rpm to uniformly disperse the organosiloxane-inorganic nanoparticles in the chlorinated polyvinyl chloride matrix, and reacting the reaction for 60-80 minutes to obtain an inorganic particle-organosiloxane-oxygen cross-linked chlorinated polyvinyl chloride, wherein the mass ratio of the organosiloxane-inorganic nanoparticles to the chlorinated polyvinyl chloride matrix is 3-4:20;
[0031] Organosiloxane-inorganic nanoparticles exhibit a typical core-shell structure at the submicroscopic level: a core of inorganic nanoparticle spheres, surrounded by an organosilicon condensation polymer. These organosiloxane-inorganic nanoparticles act as an interfacial adhesive within the CPVC matrix, forming a homogeneous phase with the CPVC matrix during processing and mixing. The inorganic nanoparticle spheres are dispersed within the CPVC matrix in a sea-island structure, enhancing overall strength and imparting excellent impact resistance.
[0032] The content of organosiloxane-inorganic nanoparticles has a significant effect on the strength of the matrix. As its content increases, the strength increases significantly. When subjected to external forces, it acts as a stress concentrator, causing a large number of silver streaks to form in the matrix around the particles. At the same time, it forces the matrix around the particles to undergo plastic deformation, absorbing impact energy, thereby playing a toughening and strengthening role.
[0033] Finally, the preparation method of high-strength chlorinated polyvinyl chloride material is as follows:
[0034] The inorganic particle-organic silicon-oxygen cross-linked chlorinated polyvinyl chloride is poured into a high-speed mixer and stirred at a speed of 800-1000 r / min until the temperature reaches 75°C-85°C. The stabilizer is then poured into the high-speed mixer and mixed until the temperature reaches 88°C-92°C. The composite lubricant, antioxidant, and pigment are then poured into the high-speed mixer and mixed until the temperature reaches 110°C-130°C. The mixture is discharged and sent to a cooling stirrer to be cooled to 30°C-40°C to obtain a high-strength chlorinated polyvinyl chloride material.
[0035] The invention first grafts hydroxypropyl methylcellulose ether by a chemical modification method, blocks cyclohexyl methacrylate and octadecyl (meth)acrylate to obtain a copolymer matrix, and crosslinks organic silicone-inorganic nanoparticles by a physical blending method, thereby improving the strength and impact resistance of the chlorinated polyvinyl chloride matrix. From a structural point of view, the organic silicone-inorganic nanoparticles and acrylate segments are distributed in the inner layer, while the chlorinated polyvinyl chloride grafted with hydroxypropyl methylcellulose ether is crosslinked therein, and the two have good compatibility.
[0036] The chlorinated polyvinyl chloride (CPVC) molecular chain, which includes hydroxypropyl groups, chlorine atoms, double bonds, oxygen-containing groups, and organosiloxane-inorganic nanoparticles, significantly inhibits the removal of HCl and blocks the formation of conjugated structures during the dehydrochlorination process. This results in high stability for the entire system. The introduction of acrylate segments improves the flexibility of the matrix, creating tough particles within the matrix. The subsequent introduction of rigid organosiloxane-inorganic nanoparticles ensures that the system maintains high strength while maintaining a certain tensile strength, completely resolving the issue of low-temperature brittleness caused by large temperature fluctuations. The resulting high-strength CPVC material exhibits uniform chlorine distribution, improved thermal stability and toughness, and significantly increased strength. The molecular structure is characterized by short chain branches and multiple branching points, which increases the polarity and rigidity of the molecular chain and enhances the interaction force of the molecular chain, thereby significantly improving the strength of the material. The introduction of acrylic ester segments improves the flexibility of the entire matrix, allowing tough particles to be present in the matrix. Rigid organosiloxane-inorganic nanoparticles are then introduced, allowing the entire system to maintain high strength while having a certain tensile strength, making the molecular structure of the material more superior, and its strength, toughness, thermal stability and temperature change resistance are greatly improved.
[0037] Compared with the prior art, the beneficial effects of this invention are:
[0038] 1) The present invention provides an inorganic particle-organic silicon-oxygen cross-linked chlorinated polyvinyl chloride material. First, hydroxypropyl methylcellulose ether is grafted by a chemical modification method, and a copolymer matrix obtained by blocking cyclohexyl methacrylate and octadecyl (meth)acrylate is obtained. Then, organosiloxane-inorganic nanoparticles are cross-linked by a physical blending method, thereby improving the strength and impact resistance of the chlorinated polyvinyl chloride matrix. The synergistic effect of the two makes the inorganic particle-organic silicon-oxygen cross-linked chlorinated polyvinyl chloride have excellent performance, and has the characteristics of short branching and multiple branching points in the molecular structure; the polarity and rigidity of the molecular chain are increased, and the interaction force of the molecular chain is enhanced, thereby significantly improving the strength of the material; the introduction of the acrylate segment improves the flexibility of the entire matrix, so that the matrix contains tough particles. Then, the rigid organosiloxane-inorganic nanoparticles are introduced, so that the entire system maintains the characteristics of high strength and has a certain tensile strength. It is particularly suitable for use in low temperature environments or extreme conditions with large ambient temperature changes, thereby expanding its scope of application.
[0039] 2) The present invention also provides a method for preparing organosiloxane-inorganic nanoparticles. These nanoparticles exhibit a typical core-shell structure at the submicroscopic level: an inner core of inorganic nanoparticle spheres and an outer shell of organosilicon polycondensate. These organosiloxane-inorganic nanoparticles act as an interfacial adhesive within a CPVC matrix, forming a homogeneous phase with the CPVC matrix during processing and mixing. The inorganic nanoparticle spheres are dispersed in the CPVC matrix as particles. The outer shell of organosilicon polycondensate is compatible with the matrix, while the inner shell of inorganic nanoparticle spheres is dispersed within the matrix, enhancing its strength.
[0040] 3) Finally, a preparation method is provided, and a high-strength chlorinated polyvinyl chloride material is prepared. The preparation method has a simple preparation process and is easy to operate. The low-temperature toughness is increased by more than 200%, the low-temperature impact strength is increased by 150-200%, and the fiber length softening point is increased by 5-15°C. DETAILED DESCRIPTION
[0041] Below in conjunction with specific embodiment, further set forth the present invention.Should be understood that these embodiments are only used to illustrate the present invention and are not used in limiting the scope of the present invention.In addition, should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall equally within the scope limited by the appended claims of the application.
[0042] Example 1
[0043] A high-strength chlorinated polyvinyl chloride material and a preparation method thereof, first preparing a chlorinated polyvinyl chloride body, specifically:
[0044] In a reactor, 100 parts of polyvinyl chloride powder and 150 parts of deionized water were added and stirred to obtain a uniformly mixed suspension. Nitrogen was introduced to remove air from the reactor. The gas in the reactor was evacuated to 0.5 MPa using a vacuum pump, and the temperature was slowly raised to 90° C. Then, 1 part of tert-butyl peroxybenzoate as an initiator was dropwise added, and chlorine was introduced at a rate of 1.8 kg / min to react the polyvinyl chloride and chlorine. After reacting for 200 minutes, 15 parts of cyclohexyl methacrylate and 10 parts of octadecyl (meth)acrylate were added, and the mixture was stirred uniformly. The temperature was slowly raised to 95° C., the gas in the reactor was reduced to a negative pressure of 1.0 MPa, and chlorine was introduced again at a rate of 4.2 kg / min. Then, 6 parts of hydroxypropyl methylcellulose ether were added, and the reaction was continued for 7 hours to obtain a crude product.
[0045] After the reaction is completed, stop heating, lower the reaction temperature to room temperature, blow out the remaining chlorine with nitrogen and let it absorb into the alkali solution tank, take out the crude product, add a certain amount of dilute alkali solution, stir for 5 minutes, then rinse with distilled water, and measure the pH value of the washing liquid with pH test paper; when the washing liquid is neutral, filter it and pour tetrahydrofuran into it to completely dissolve it, then add methanol to fully precipitate it, and then filter it; finally, place it in a vacuum drying oven and dry it at 40°C to constant weight to obtain chlorinated polyvinyl chloride body.
[0046] Furthermore, inorganic nanoparticles are prepared, specifically by:
[0047] 10 parts of graphene oxide were dispersed in 100 parts of deionized water, and the pH was adjusted to 8.0 with NaOH solution to obtain a mixed solution; the mixed solution was then transferred to a polytetrafluoroethylene hydrothermal reactor for hydrothermal reaction to obtain two-dimensional reduced graphene oxide; the two-dimensional reduced graphene oxide was freeze-dried in a freeze dryer at a temperature of -30°C for 24 hours and ground to obtain three-dimensional reduced graphene oxide; 30 parts of nano-SiO2 and 10 parts of three-dimensional reduced graphene oxide were evenly mixed to obtain inorganic nanoparticles.
[0048] The preparation method of the strength enhancer organosiloxane-inorganic nanoparticles is specifically as follows:
[0049] In a reaction kettle equipped with a stirring paddle, a thermometer, and a condenser, 20 parts of vinyltrimethoxysiloxane, 10 parts of mono(meth)acrylate-terminated polysiloxane, and 20 parts of anilinemethyltriethoxysiloxane are mixed with 100 parts of ethyl acetate and stirred evenly. Then, 1 part of azobisisobutyronitrile as an initiator is added dropwise, and the temperature is raised to 90°C for reaction for 18 hours. The reaction is terminated, cooled to room temperature, and low-temperature drying is performed to remove residual small molecules in the reaction system to obtain an organosilicon polycondensate. Then, 20 parts of inorganic nanoparticles and 80 parts of the organosilicon polycondensate are mixed in an alcohol ether solution by a solution blending method and stirred at high speed for 60 minutes to fully crosslink the inorganic nanoparticles in the organosilicon polycondensate to obtain organosiloxane-inorganic nanoparticles.
[0050] The organosiloxane-inorganic nanoparticles are added to the chlorinated polyvinyl chloride matrix to obtain inorganic particle-organosiloxane oxygen cross-linked chlorinated polyvinyl chloride, specifically:
[0051] 100 parts of chlorinated polyvinyl chloride (CPCV) matrix and 15 parts of organosiloxane-inorganic nanoparticles were added to a reaction kettle. Under nitrogen protection, the temperature was raised to 140°C and the stirring speed was 500 rpm to uniformly disperse the organosiloxane-inorganic nanoparticles in the CPCV matrix. The reaction was continued for 80 minutes to obtain inorganic particle-organosiloxane-oxygen cross-linked CPCV.
[0052] Finally, the preparation method of high-strength chlorinated polyvinyl chloride material is as follows:
[0053] 100 parts of inorganic particle-organic silicone cross-linked chlorinated polyvinyl chloride are poured into a high-speed mixer and stirred at a speed of 1000 r / min until the temperature reaches 85°C. Then, 8 parts of calcium zinc stabilizer are poured into the high-speed mixer and continued to mix until the temperature reaches 92°C. Then, 2 parts of oxidized polyethylene wax, 4 parts of ethylene bisstearamide, 0.3 parts of diisooctyl diphenylamine, and 2 parts of titanium dioxide are poured into the high-speed mixer and continued to mix until the temperature reaches 130°C. The material is discharged and the mixture is sent to a cooling stirrer to be cooled to 30°C to obtain a high-strength chlorinated polyvinyl chloride material.
[0054] Example 2
[0055] A high-strength chlorinated polyvinyl chloride material and a preparation method thereof, first preparing a chlorinated polyvinyl chloride body, specifically:
[0056] In a reactor, 120 parts of polyvinyl chloride powder and 250 parts of deionized water were added and stirred to obtain a uniformly mixed suspension. Nitrogen was introduced to remove air from the reactor. The gas in the reactor was evacuated to 0.6 MPa using a vacuum pump, and the temperature was slowly raised to 8° C. Then, 2 parts of tert-butyl peroxybenzoate as an initiator were dropwise added. Chlorine was introduced at a rate of 2.0 kg / min to react the polyvinyl chloride and chlorine. After reacting for 200 minutes, 8 parts of cyclohexyl methacrylate and 20 parts of octadecyl (meth)acrylate were added and stirred uniformly. The temperature was slowly raised to 95° C. The gas in the reactor was reduced to a negative pressure of 1.0 MPa. Chlorine was introduced a second time at a rate of 4.0 kg / min, and 8 parts of hydroxypropyl methylcellulose ether were added. The reaction was continued for 7 hours to obtain a crude product.
[0057] After the reaction is completed, stop heating, lower the reaction temperature to room temperature, blow out the remaining chlorine with nitrogen and let it absorb into the alkali solution tank, take out the crude product, add a certain amount of dilute alkali solution, stir for 5 minutes, then rinse with distilled water, and measure the pH value of the washing liquid with pH test paper; when the washing liquid is neutral, filter it and pour tetrahydrofuran into it to completely dissolve it, then add methanol to fully precipitate it, and then filter it; finally, place it in a vacuum drying oven and dry it at 40°C to constant weight to obtain chlorinated polyvinyl chloride body.
[0058] Furthermore, inorganic nanoparticles are prepared, specifically by:
[0059] 10 parts of graphene oxide were dispersed in 100 parts of deionized water, and the pH was adjusted to 8.0 with a NaOH solution to obtain a mixed solution; the mixed solution was then transferred to a polytetrafluoroethylene hydrothermal reactor for a hydrothermal reaction to obtain two-dimensional reduced graphene oxide; the two-dimensional reduced graphene oxide was freeze-dried in a freeze dryer at a temperature of -30°C for 24 hours and ground to obtain three-dimensional reduced graphene oxide; 30 parts of nano-SiO2 and 10 parts of three-dimensional reduced graphene oxide were uniformly mixed to obtain inorganic nanoparticles;
[0060] The preparation method of the strength enhancer organosiloxane-inorganic nanoparticles is specifically as follows:
[0061] In a reaction kettle equipped with a stirring paddle, a thermometer, and a condenser, 20 parts of vinyl trimethoxysiloxane, 10 parts of mono(meth)acrylate-terminated polysiloxane, and 20 parts of aniline methyl triethoxysiloxane are mixed with 100 parts of ethyl acetate and stirred evenly. 0.5 parts of azobisisobutyronitrile as an initiator are then added dropwise, and the temperature is raised to 85° C. to react for 19 hours. The reaction is terminated, cooled to room temperature, and then dried at low temperature to remove residual small molecules in the reaction system to obtain an organosilicon polycondensate. 10 parts of inorganic nanoparticles and 90 parts of the organosilicon polycondensate are then mixed in an alcohol ether solution by a solution blending method and stirred at high speed for 60 minutes to fully crosslink the inorganic nanoparticles in the organosilicon polycondensate to obtain organosiloxane-inorganic nanoparticles.
[0062] Then, the organosiloxane-inorganic nanoparticles are added to the chlorinated polyvinyl chloride matrix to obtain inorganic particle-organosiloxane oxygen cross-linked chlorinated polyvinyl chloride, specifically:
[0063] 100 parts of chlorinated polyvinyl chloride (CPCV) matrix and 20 parts of organosiloxane-inorganic nanoparticles were added to a reaction kettle. Under nitrogen protection, the temperature was raised to 180°C and the stirring speed was 500 rpm to uniformly disperse the organosiloxane-inorganic nanoparticles in the CPCV matrix. The reaction was continued for 80 minutes to obtain inorganic particle-organosiloxane-oxygen cross-linked CPCV.
[0064] Finally, the preparation method of high-strength chlorinated polyvinyl chloride material is as follows:
[0065] 120 parts of inorganic particle-organic silicon-oxygen cross-linked chlorinated polyvinyl chloride are poured into a high-speed mixer and stirred at a speed of 900 r / min until the temperature reaches 85°C. Then, 10 parts of organotin stabilizer are poured into the high-speed mixer and mixed until the temperature reaches 92°C. Then, 2 parts of oxidized polyethylene wax, 2 parts of ethylene bisstearamide, 0.3 parts of 2,6-tert-butyl-4-methylphenol, and 2.5 parts of titanium dioxide are poured into the high-speed mixer and mixed until the temperature reaches 130°C. The material is discharged and the mixture is sent to a cooling stirrer to be cooled to 40°C to obtain a high-strength chlorinated polyvinyl chloride material.
[0066] Example 3
[0067] A high-strength chlorinated polyvinyl chloride material and a preparation method thereof, first preparing a chlorinated polyvinyl chloride body, specifically:
[0068] In a reactor, 100 parts of polyvinyl chloride powder and 200 parts of deionized water were added and stirred to obtain a uniformly mixed suspension. Nitrogen was introduced to remove air from the reactor. The gas in the reactor was evacuated to 0.5 MPa using a vacuum pump, and the temperature was slowly raised to 85° C. Then, 1 part of tert-butyl peroxybenzoate as an initiator was added dropwise, and chlorine was introduced at a rate of 2.1 kg / min to react the polyvinyl chloride and chlorine. After reacting for 200 minutes, 10 parts of cyclohexyl methacrylate and 15 parts of octadecyl (meth)acrylate were added, and the mixture was stirred uniformly. The temperature was slowly raised to 100° C., the gas in the reactor was reduced to a negative pressure of 0.9 MPa, chlorine was introduced at a rate of 4.0 kg / min for a second time, 7 parts of hydroxypropyl methylcellulose ether were added, and the reaction was continued for 6 hours to obtain a crude product.
[0069] After the reaction is completed, stop heating, lower the reaction temperature to room temperature, blow out the remaining chlorine with nitrogen and let it absorb into the alkali solution tank, take out the crude product, add a certain amount of dilute alkali solution, stir for 5 minutes, then rinse with distilled water, and measure the pH value of the washing liquid with pH test paper; when the washing liquid is neutral, filter it and pour tetrahydrofuran into it to completely dissolve it, then add methanol to fully precipitate it, and then filter it; finally, place it in a vacuum drying oven and dry it at 40°C to constant weight to obtain chlorinated polyvinyl chloride body.
[0070] Furthermore, inorganic nanoparticles are prepared, specifically by:
[0071] 10 parts of graphene oxide were dispersed in 100 parts of deionized water, and the pH was adjusted to 8.0 with a NaOH solution to obtain a mixed solution; the mixed solution was then transferred to a polytetrafluoroethylene hydrothermal reactor for a hydrothermal reaction to obtain two-dimensional reduced graphene oxide; the two-dimensional reduced graphene oxide was freeze-dried in a freeze dryer at a temperature of -40°C for 24 hours and ground to obtain three-dimensional reduced graphene oxide; 30 parts of nano-SiO2 and 10 parts of three-dimensional reduced graphene oxide were uniformly mixed to obtain inorganic nanoparticles;
[0072] The preparation method of the strength enhancer organosiloxane-inorganic nanoparticles is specifically as follows:
[0073] In a reaction kettle equipped with a stirring paddle, a thermometer, and a condenser, 20 parts of vinyl trimethoxysiloxane, 10 parts of mono(meth)acrylate-terminated polysiloxane, and 20 parts of aniline methyl triethoxysiloxane are mixed with 100 parts of ethyl acetate and stirred evenly. Then, 1 part of azobisisobutyronitrile as an initiator is added dropwise, and the temperature is raised to 90° C. to react for 20 hours. The reaction is stopped, cooled to room temperature, and low-temperature drying is performed to remove residual small molecules in the reaction system to obtain an organosilicon polycondensate. Then, 15 parts of inorganic nanoparticles and 85 parts of the organosilicon polycondensate are mixed in an alcohol ether solution by a solution blending method and stirred at high speed for 60 minutes to fully crosslink the inorganic nanoparticles in the organosilicon polycondensate to obtain organosiloxane-inorganic nanoparticles.
[0074] Then, the organosiloxane-inorganic nanoparticles are added to the chlorinated polyvinyl chloride matrix to obtain inorganic particle-organosiloxane oxygen cross-linked chlorinated polyvinyl chloride, specifically:
[0075] 100 parts of chlorinated polyvinyl chloride (CPCV) matrix and 18 parts of organosiloxane-inorganic nanoparticles were added to a reaction kettle. Under nitrogen protection, the temperature was raised to 180°C and the stirring speed was 500 rpm to uniformly disperse the organosiloxane-inorganic nanoparticles in the CPCV matrix. The reaction was continued for 70 minutes to obtain inorganic particle-organosiloxane-oxygen cross-linked CPCV.
[0076] Finally, the preparation method of high-strength chlorinated polyvinyl chloride material is as follows:
[0077] 110 parts of inorganic particle-organic silicone cross-linked chlorinated polyvinyl chloride are poured into a high-speed mixer and stirred at a speed of 1000 r / min until the temperature reaches 80°C. Then, 10 parts of calcium zinc stabilizer are poured into the high-speed mixer and continued to mix until the temperature reaches 90°C. Subsequently, 2 parts of oxidized polyethylene wax, 4 parts of ethylene bisstearamide, 0.3 parts of diisooctyl diphenylamine, and 2 parts of titanium dioxide are poured into the high-speed mixer and continued to mix until the temperature reaches 120°C. The material is discharged and the mixture is sent to a cooling stirrer to be cooled to 35°C to obtain a high-strength chlorinated polyvinyl chloride material.
[0078] Comparative Example 1: Chlorinated polyvinyl chloride substrate was not grafted with hydroxypropyl methylcellulose ether, but was directly blocked with acrylate, and the rest was the same as in Example 1;
[0079] Comparative Example 2: Inorganic nanoparticles were directly added to the chlorinated polyvinyl chloride matrix without preparing the inorganic nanoparticles and the organosilicon polycondensate into organosiloxane-inorganic nanoparticles. Other aspects were the same as in Example 1.
[0080] Comparative Example 3: Ordinary nano-SiO2 and ordinary graphene oxide as inorganic nanoparticles are directly added to the organosilicon polycondensate to prepare organosiloxane-inorganic nanoparticles, and the rest is the same as in Example 1;
[0081] Comparative Example 4: Chlorinated polyvinyl chloride matrix was not grafted with hydroxypropyl methylcellulose ether, but was directly prepared by blocking acrylate. Ordinary nano-SiO2 and ordinary graphene oxide were directly added as inorganic nanoparticles to the organosilicon polycondensate to prepare organosiloxane-inorganic nanoparticles. Other aspects were the same as in Example 1.
[0082] Comparative Example 5: The product in Example 4 involved in the preparation method of the chlorinated polyvinyl chloride modified material disclosed in Chinese Patent Publication No. CN105175964B.
[0083] Performance test
[0084] 1. Thermal stability test
[0085] Dynamic thermal stability testing was conducted using a Haake rheometer. The mixer temperature was set at 180-210°C, the rotor speed was 30 rpm, and the feed volume was 55 g. The mixed material was weighed and added to the mixer. The rheometer was started and the test was continued until the torque remained constant for 5 minutes. The Vicat softening point was determined according to the B50 method specified in GB / T 8802-2001.
[0086] The high-strength chlorinated polyvinyl chloride materials obtained in Examples 1-3 and Comparative Examples 1-5 were subjected to thermal stability tests, and the results of the stability time at 200°C are shown in Table 1. This is because the introduction of branches into the macromolecular chain has the characteristics of short branches and multiple branching points in the molecular structure, which increases the polarity and rigidity of the molecular chain, enhances the interaction force of the molecular chain, and inhibits the dechlorination reaction of the double bonds and partial chlorine structures on the molecular chain during the polymer thermoforming process, thereby inhibiting the self-catalytic degradation reaction of chlorinated polyvinyl chloride during high-temperature processing, and significantly improving the heat resistance and high-temperature stability of the chlorinated polyvinyl chloride bodies of Examples 1-3.
[0087] As can be seen from Table 1, when the chlorine content is not much different, the Vicat Vicat softening points of Examples 1-3 not only maintain a high level, but also their stability time at high temperature is significantly improved. The organic combination of chemical grafting and physical blending, as well as organosiloxane-inorganic nanoparticles, effectively improves the heat resistance of the chlorinated polyvinyl chloride matrix, expands the range of melting temperature and thermal decomposition temperature, and can achieve a stability time of about 100 minutes at 200°C, greatly reducing the difficulty of plasticizing chlorinated polyvinyl chloride.
[0088] The Vicat softening point is increased by chemically grafting and acrylate-blocked CPVC, along with the addition of organosiloxane-inorganic nanoparticles. Therefore, according to blending theory, its Vicat softening point is higher than that of CPVC. Furthermore, the core-shell structure of the organosiloxane-inorganic nanoparticles further enhances the material's thermal stability. This increased Vicat softening point means the material is more capable of maintaining its shape and properties in high-temperature environments, which also helps improve its processing properties.
[0089] Table 1 Thermal stability test results of high strength chlorinated polyvinyl chloride materials
[0090]
[0091]
[0092] 2. Mechanical properties test results
[0093] The cooled mixture was fed into a twin-screw extruder for melt extrusion. Standard specimens of chlorinated polyvinyl chloride (CPV) were obtained by hot-cutting the die head and tested for mechanical properties. Elastic modulus and elongation at break were determined using a universal tensile tester in accordance with GB / T 1040.1-2018 to characterize the plasticizing efficiency of the CPV-modified material. The tensile rate was 10 mm / min. Impact strength was tested in accordance with GB / T 1043.1-2008. The structures are shown in Table 2.
[0094] Table 2 Mechanical properties test results of high strength chlorinated polyvinyl chloride materials
[0095]
[0096] The impact strength of the products prepared in Examples 1-3 is enhanced by the addition of organosiloxane-inorganic nanoparticles. This is because the organosiloxane-inorganic nanoparticles can be added to the chlorinated polyvinyl chloride matrix as an elastomer and dispersed in the continuous phase of the matrix in a uniform granular state, thereby forming a so-called network cross-linked structure with macroscopic homogeneous phase and microscopic phase separation. When an external force is applied, the elastic particles act as stress concentrators, inducing a large number of silver streaks and shear bands in the matrix. The generation and development of silver streaks and shear bands consumes a large amount of energy, thereby increasing the impact strength of the elastomer system of Examples 1-3. The addition of flexible particles to the chlorinated polyvinyl chloride matrix grafted with hydroxypropyl methylcellulose ether and block acrylate significantly increases the elongation at break. When the impact strength is significantly increased, the fibers will fill in the areas where a large number of silver streaks and shear bands are generated and continuously repair them, thereby significantly improving the elongation at break. Therefore, it can be seen from Table 2 that compared with comparative examples 1-5, the elongation at break and impact strength of Examples 1-3 are significantly improved; the introduction of acrylate segments improves the flexibility of the entire matrix, so that tough particles are present in the matrix, and then the introduction of rigid organosiloxane-inorganic nanoparticles allows the entire system to maintain the characteristics of high strength while having a certain tensile strength, which also makes the molecular structure of the material more superior, and its strength, thermal stability and heat resistance are greatly improved; the inherent defect of chlorinated polyvinyl chloride, which is poor impact resistance, is improved, and its scope of application is expanded.
[0097] 3. Test results of mechanical properties at low temperature
[0098] The standard plastic samples of Examples 1-3 and Comparative Examples 1-5 were placed in a temperature range of -20°C and 60°C, alternating between hot and cold for 24 hours. After three months, their mechanical properties were tested. The structures are shown in Table 3.
[0099] Table 3 Mechanical properties test results of high strength chlorinated polyvinyl chloride materials under variable temperature
[0100]
[0101] As can be seen from Table 3, after long-term storage at variable temperatures, the strength and tensile strength of Examples 1-3 and Comparative Examples 1-5 both decrease to a certain extent. Compared with Examples 1-3, the decrease in the Comparative Examples is greater. This is because the brittleness of CPVC changes significantly under extreme temperature fluctuations, while Examples 1-3, to which flexible particles are added, can resist such extreme changes. The addition of hydroxypropyl methylcellulose ether makes the various polar groups of the material evenly distributed, thus avoiding the generation of large cracks to a certain extent, making the decrease in tensile strength less obvious. The addition of organosiloxane-inorganic nanoparticles makes it very compatible with the matrix at low temperatures, and there is no problem of agglomeration, granulation, or precipitation, so that the strength of the matrix can still be maintained in a good state. However, since the added inorganic nanoparticles in Comparative Examples 2-4 were not specially treated, especially in Comparative Example 2, because there was no promotion of compatibility of the organic condensation polymer, the rigid particles precipitated to varying degrees, and the strength of the matrix could not be effectively enhanced, resulting in a significant decrease in impact strength. Therefore, hydroxypropyl methylcellulose ether and acrylate-crosslinked chlorinated polyvinyl chloride were chemically grafted into the matrix, and organosiloxane-inorganic nanoparticles were added. These three elements promote each other, thereby improving the overall performance of the prepared high-strength chlorinated polyvinyl chloride material, especially significantly enhancing the performance at low temperatures.
[0102] The above description is only used to illustrate the technical solution of the present invention and is not intended to limit it. Any modifications and changes made to the technical solution of the present invention by ordinary persons in the art shall still fall within the scope of the present invention as long as they do not depart from the overall concept of the present invention.
Claims
1. A high-strength chlorinated polyvinyl chloride material, characterized in that: The high-strength chlorinated polyvinyl chloride material is prepared from the following raw materials in parts by weight: 100-120 parts of inorganic nanoparticle-organic silicon oxygen cross-linked chlorinated polyvinyl chloride; 8-10 parts of stabilizer; 4.0-6.0 parts of composite lubricant; 0.3-0.5 parts of antioxidant; 1.5-2.5 parts of pigment; The inorganic nanoparticle-organic silicon oxygen cross-linked chlorinated polyvinyl chloride is prepared from a chlorinated polyvinyl chloride matrix, organic silicon oxane and inorganic nanoparticles. The chlorinated polyvinyl chloride matrix is prepared by chlorinating polyvinyl chloride, blocking acrylate and grafting hydroxypropyl methylcellulose ether.
2. The high-strength chlorinated polyvinyl chloride material according to claim 1, characterized in that: The chlorinated polyvinyl chloride body and its preparation method are specifically as follows: S001, add polyvinyl chloride powder and deionized water to a reactor, stir and mix to obtain a uniform suspension, introduce nitrogen to remove air in the reactor, use a vacuum pump to evacuate the gas in the reactor to negative pressure, slowly raise the temperature to 85-90°C, then dropwise add initiator tert-butyl peroxybenzoate, introduce chlorine, and react polyvinyl chloride and chlorine under a certain pressure. After reacting for 150-200 minutes, add cyclohexyl methacrylate and octadecyl (meth)acrylate, stir evenly, slowly raise the temperature to 95-100°C, introduce chlorine for the second time, add hydroxypropyl methylcellulose ether, and continue to react for 5-7 hours to obtain a crude product; S002, after the reaction is completed, stop heating, lower the reaction temperature to room temperature, blow out the remaining chlorine with nitrogen to the alkali solution tank for absorption, take out the crude product, add a certain amount of dilute alkali solution, stir for 5 minutes, then rinse with distilled water, and measure the pH value of the washing liquid with pH test paper; when the washing liquid is neutral, filter it and pour in tetrahydrofuran to completely dissolve it, then add methanol to fully precipitate it, and then filter it; obtain chlorinated polyvinyl chloride with hydroxypropyl methylcellulose ether grafted on the side chain of block acrylate, recorded as chlorinated polyvinyl chloride body, and finally place it in a vacuum drying oven and dry it at 40°C to constant weight.
3. The high-strength chlorinated polyvinyl chloride material according to claim 1, characterized in that: The organosiloxane-inorganic nanoparticles are added to the chlorinated polyvinyl chloride matrix to obtain the inorganic particle-organosiloxane oxygen cross-linked chlorinated polyvinyl chloride, specifically: Chlorinated polyvinyl chloride matrix and organosiloxane-inorganic nanoparticles are added into a reaction kettle, and under nitrogen protection, the temperature is raised to 130-180° C., and the stirring speed is 500 rpm, so that the organosiloxane-inorganic nanoparticles are uniformly dispersed in the chlorinated polyvinyl chloride matrix, and the reaction is carried out for 60-80 minutes to obtain inorganic particle-organosiloxane-oxygen cross-linked chlorinated polyvinyl chloride; wherein the mass ratio of the organosiloxane-inorganic nanoparticles to the chlorinated polyvinyl chloride matrix is 3-4:
20.
4. The high-strength chlorinated polyvinyl chloride material according to claim 3, characterized in that: Organic siloxane-inorganic nanoparticles are used as strength enhancers, and the preparation method thereof is specifically as follows: S101, in a reaction kettle equipped with a stirring blade, a thermometer, and a condenser, vinyl trimethoxysiloxane, mono (meth) acrylate-terminated polysiloxane, and aniline methyl triethoxysiloxane, add an appropriate amount of ethyl acetate, mix, stir evenly, then dropwise add initiator azobisisobutyronitrile, raise the temperature to 80-90° C. and react for 18-20 hours; stop the reaction, cool to room temperature, and dry at low temperature to remove small molecular substances remaining in the reaction system, so as to obtain an organosilicon polycondensate with a molecular weight of 30,000-40,000; S102, mixing the inorganic nanoparticles and the organosilicon polycondensate in an alcohol ether solution by a solution blending method, stirring at a high speed for 60 minutes, so that the inorganic nanoparticles are fully cross-linked in the organosilicon polycondensate, to obtain organosiloxane-inorganic nanoparticles; The mass ratio of the mono(meth)acrylate-terminated polysiloxane, anilinemethyl triethoxysiloxane and vinyl trimethoxysiloxane is 1:2:2; the mass content of the nano-silicon dioxide is 10-20% of the organosilicon polycondensate, and the amount of the initiator azobisisobutyronitrile is 1-2% of the total amount of the siloxane.
5. The high-strength chlorinated polyvinyl chloride material according to claim 4, characterized in that: The inorganic nanoparticles are a mixture of nano-SiO2 and graphene oxide, and the particle size is 20 to 30 nm. The preparation method is specifically as follows: S201, dispersing graphene oxide in water, adjusting the pH to alkaline with a NaOH solution, and obtaining a mixed solution; then transferring the mixed solution into a polytetrafluoroethylene hydrothermal reactor for hydrothermal reaction to obtain two-dimensional reduced graphene oxide; S202, using a freeze drying method to convert the two-dimensional reduced graphene oxide into three-dimensional reduced graphene oxide, specifically as follows: freeze drying the two-dimensional reduced graphene oxide in a freeze dryer at a temperature of -30°C to -40°C for 24 hours, and grinding to obtain three-dimensional reduced graphene oxide; S203, nano-SiO2 and three-dimensional reduced graphene oxide are mixed evenly in a mass ratio of 3:1 to obtain inorganic nanoparticles.
6. The high-strength chlorinated polyvinyl chloride material according to claim 1, characterized in that: The stabilizer is at least one of an organic tin stabilizer and a calcium zinc stabilizer; The composite lubricant is a mixture of oxidized polyethylene wax and ethylene bisstearamide in a mass ratio of 1:1 to 2; The antioxidant comprises at least one of p-diisooctyldiphenylamine and 2,6-tert-butyl-4-methylphenol; and the pigment is titanium dioxide.
7. The high-strength chlorinated polyvinyl chloride material according to claim 2, characterized in that: The heating rate is controlled at 0.07-0.12°C / min, and the temperature is raised to 85-90°C. Then, chlorine is passed through at a rate of 1.8-2.1kg / min, and the pressure in the kettle is controlled at 0.5-0.6MPa. The second chlorine chlorination is carried out at a rate of 3.8-4.2kg / min, and the heating rate is controlled at 0.07-0.12°C / min, and the temperature is raised to 95-100°C. The pressure in the kettle is controlled at 0.6-1.0Mpa. The polyvinyl chloride powder is 100-120 parts, the tert-butyl perbenzoate is 1-2 parts, and the deionized water is 150-250 parts; the mass ratio of hydroxypropyl methylcellulose ether, cyclohexyl methacrylate, octadecyl (meth)acrylate and polyvinyl chloride powder is 5-8:8-15:10-20:100-120.
8. The high-strength chlorinated polyvinyl chloride material according to claim 1, characterized in that: The preparation method of high-strength chlorinated polyvinyl chloride material is specifically as follows: Pour the inorganic particle-organic silicon oxygen cross-linked chlorinated polyvinyl chloride into a high-speed mixer, stir and mix at a speed of 800-1000r / min until the temperature reaches 75°C-85°C, then pour the stabilizer into the high-speed mixer and continue to mix until the temperature reaches 88°C-92°C, then pour the composite lubricant, antioxidant, and pigment into the high-speed mixer and continue to mix until the temperature reaches 110°C-130°C, discharge the material, and send the mixed material into a cooling stirrer to cool it to 30°C-40°C, so as to obtain a high-strength chlorinated polyvinyl chloride material.
Citation Information
Patent Citations
Preparation Method of Chlorinated Polyvinyl Chloride Modified Material
CN105175964B
A method for improving the processing properties of chlorinated polyvinyl chloride resin
CN113683851B
A high-strength insulating CPVC material and its preparation method
CN114149649B